Emergence of helicity in rotating stratified turbulence - Marino, Raffaele (2013)
We perform numerical simulations of decaying rotating stratified turbulence and show, in the Boussinesq framework, that helicity (velocity-vorticity correlation), as observed in supercell storms and hurricanes, is spontaneously created due to an interplay between buoyancy and rotation common to large-scale atmospheric and oceanic flows. Helicity emerges from the joint action of eddies and of inertia-gravity waves (with inertia and gravity with respective associated frequencies f and N), and it occurs when the waves are sufficiently strong. For N/ f <3 the amount of helicity produced is correctly predicted by a quasilinear balance equation. Outside this regime, and up to the highest Reynolds number obtained in this study, namely Re≈10 000, helicity production is found to be persistent forN/f as large as ≈17, and for ReFr 2 and ReRo 2, respectively, as large as ≈100 and ≈24000.